Ruby Holler - Creech, Sharon (New York : Scholastic, 2003)
Thirteen-year-old fraternal twins Dallas and Florida have grown up in a terrible orphanage but their lives change forever when an eccentric but sweet older couple invites them each on an adventure, beginning in an almost magical place called Ruby Holler.
Originally published: New York : HarperCollinsPublishers, c2002.
Keywords: Orphans -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Wood carvers -- Fiction; Country life -- Fiction; Voyages and travels -- Fiction